Evaluation of Sedation Outcomes Following Increased Dexmedetomidine Use in the ICU. (April 2020) - Schuler, Brian R.; Kovacevic, Mary P.; Dube, Kevin M.; Szumita, Paul M.; DeGrado, Jeremy R.
Abstract : Objective: To evaluate sedation practices following a dexmedetomidine guideline update in the ICU. Design: Single-center, retrospective chart review. Setting: Tertiary academic medical center. Patients: Patients were included in this analysis if they were admitted to the ICU and were ordered for continuous infusion sedatives or opioids from September to November 2016 (PRE) and from September to November 2017 (POST). Patients were excluded from this analysis if they met any of the following criteria: mechanical ventilation less than 12 hours, admitted with acute neurologic injury, burn of greater than 20% total body surface area, chronic tracheostomy, admitted to the neuroscience or cardiac surgery ICU, on extracorporeal membrane oxygenation support, or received an infusion of neuromuscular blockers. Interventions: Patients admitted during a restricted dexmedetomidine prescribing guideline were compared with patients admitted during an expanded prescribing guideline. Measurements and Main Results: Of the 1, 426 patients evaluated for inclusion, 427 patients met the criteria in this analysis. Of these, 217 patients were in the PRE and 210 patients in the POST. A majority of patients were excluded for admission to neuroscience or cardiac surgery ICU. Dexmedetomidine was used in 13.8% of encounters in the PRE and 51.9% of encounters in the POST ( p < 0.001). The median duration of mechanical ventilation was 49 hours (24–110 hr) in the PRE and 47.5 hours (26–98 hr) in the POST ( p = 0.8). ICU length of stay was a median of 136 and 121 hours in the PRE and POST, respectively ( p = 0.2). The median hospital length of stay was 296 and 326 hours in the PRE and POST, respectively ( p = 0.35). After controlling for possible confounders, ventilation time remained unchanged between the PRE and POST ( p = 0.98). Conclusions: The expansion of a hospital dexmedetomidine prescribing guideline resulted in an increased use of dexmedetomidine but was not associated with a difference in length of mechanical ventilation.